DEVELOPMENT OF IT OUTSOURCING IN UKRAINE: A PROSPECT OF THE BRAIN DRAIN REDUCTION - Nataliia Marynenko; Halyna Tsikh; Iryna Kramar (Economic Review)
Ukraine is faced by a devastating problem of economically active population emigration, which has reduced the labor force in the country by 5-8% in the last two years and demonstrated a negative impact on the potential Gross Domestic Product (GDP). Despite this, Ukraine is one of the leading software development centers in Central and Eastern Europe and ranks fourth in the export of information technology (IT) products and services in the world nowadays. The IT industry is one of the four priority sectorsfor Ukraine’s export strategy, it is one of the most perspective, dynamic and innovative branches of Ukraine’s economy. Professional expertise, cost effectiveness and high standard technical education make this industry attractive also in terms of employing Ukraine’s own intellectual resources within the country. The article aims to characterize the state of affairs, potential and prospects for the development of the Ukrainian IT outsourcing market as well as to analyze and evaluate it including comparison with foreign practice. Research methods used are as follows: desk research, inductive and deductive methods, abstract and logical method, system approach,  analysis and synthesis, empirical methods, and statistical analysis. The essence of IT outsourcing, its types, aims and main advantages of use are revealed in the article. The features of IT outsourcing industry trends both in Ukraine and the world practice are researched. Competitive advantages of Ukraine in the world IT outsourcing market are identified. Challenges, obstacles, risks as well as potentials and prospects of IT outsourcing development are determined and analyzed. Recommendations for the brain drain reduction due to the IT industry progress are offered and its impact on the potential GDP growth and economic development of Ukraine as a whole is provided.